A influência do líder de projetos na transmissão da cultura em uma organização em rede - Esteves, Maria Fernanda Freitas (2003)
This essay has as main objective to analyze how the leaders of an organization, that base its activities on a network structure transmit the corporate culture to its affiliated companies. Also, it intends to investigate if the leaders changed their role in function of the organizational changes in the period considered by some authors as pos-modern. As corporate culture is wide and complex, It was focused on the effects on the affiliated company caused by the assimilation of corporate missions and objectives, the administration style predominant of the corporate and its influence in the management of projects among the protagonists of those different organizations. It was used a theoretical-empiric system that tried to define the culture concept through symbolic universe study, the leadership and its relationship with organizational structures and sources of power and control, culture and leadership in the Brazilian context; and the network concept in the organization exploring the administration aspects, power and control in this type of organization. lhis research is a case study based on a not for profit organization, which develops social projects with focus on education. It is an exploratory and descriptive study. lhe qualitative method was used to present this research. lhe research focus on the qualitative method because was not possible to quantify many of the observations. lhe technique of participant observation and semi-structured interviews were used, besides the documentary analysis. lhis technique facilitated an investigation that characterized the descriptive and interpretative participation of the interviewees in relation to the phenomenon observed. lhe data gathered and the fundamentionism analysis, led to believe that a network organization leader transmits the organizational culture with the same emphasis of a traditional organization leader. It is believed that this work will awake the academic community's interest, once the cultural aspects are usually researched inside of the organization and what stood out here are the organization context and the role that a leader assumes in the administration of the activities accomplished by third party. Would the Brazilian's manager give up the power and control that a hierarchical structure concede to him, to work in a relationship of equality with representatives of other organizations?